Pendampingan Peran Orang Tua dalam Mengoptimalkan Kecerdasan Anak Melalui Matematika - Fazriansyah, Muh Fajar; Sirri, Evi Latifatus (Jaanur ElBarik Indonesia, 2025)
This community service program aims to improve parents' understanding and skills in supporting optimal child intelligence development. The methods used include outreach or counseling, interactive discussions, and simulations. The results of the mentoring activities are an increase in the understanding and awareness of parents in Sarimukti Village regarding the importance of their role in optimizing children's intelligence. Participants experienced increased knowledge about factors that influence intelligence, as well as simple ways to introduce mathematics through daily activities. Although the direct impact on children cannot yet be measured quantitatively, early indications show an increase in children's interest in learning when accompanied by parents. This shows that this training has the potential to form a more educational parenting pattern and support the development of children's intelligence in a sustainable manner.